2019
DOI: 10.3389/fnins.2018.01002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights Into Memory-Enhancing Metabolites of Nicotine in Brain: A Systematic Review

Abstract: Background: The alleged procognitive effects of nicotine and its metabolites in brain are controversial.Objective: Here, we review the pharmacologically active metabolites of nicotine in brain and their effects on neuronal mechanisms involving two main cognitive domains, i.e., learning and memory.Methods: We searched Embase, Medline via PubMed, Scopus, and Web of Science databases for entries no later than May 2018, and restricted the search to articles about nicotine metabolites and cognitive behavior or cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 99 publications
(123 reference statements)
0
16
0
Order By: Relevance
“…Therefore, it is hypothesized that the stimulation of nAChRs by nicotine or its analogs activates the PI3K/Akt signaling pathway, which, in turn, regulates learning and memory processes (42,45). Indeed, acute and chronic administration of nicotine was reported to improve cognitive impairment in patients with AD (46)(47)(48). Moreover, acute nicotine administration during electroencephalography (EEG) performed in patients with ad who received cholinesterase inhibitors was found to shift the EEG readings towards normal levels (49).…”
Section: Benefits Of Nicotine In Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Therefore, it is hypothesized that the stimulation of nAChRs by nicotine or its analogs activates the PI3K/Akt signaling pathway, which, in turn, regulates learning and memory processes (42,45). Indeed, acute and chronic administration of nicotine was reported to improve cognitive impairment in patients with AD (46)(47)(48). Moreover, acute nicotine administration during electroencephalography (EEG) performed in patients with ad who received cholinesterase inhibitors was found to shift the EEG readings towards normal levels (49).…”
Section: Benefits Of Nicotine In Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Clinically apply nicotine as a treatment of learning and memory impairment and its underlying disorders, biologically active metabolite is more than just a biomarker of nicotine consumption and has potentially therapeutic value in the treatment of learning and memory declines. 13 The percentage of tooth loss by age group in Monmata village of Kecamatan Lhoong ( Table 2) showed that tooth loss in the smokers group occurred in the age range 56-65 years old where age was included in the elderly so that factors can affect tooth loss. The more increase the age, the greater the periodontal tissue damage that occurs when treatment is not conduct.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in this area have shown that these pathways promote neuronal survival, proliferation, and neurite growth as well as neurotransmitter release in the brain and other tissues ( Eneroth et al, 1977 ; Fuxe et al, 1979 ; Aizenman et al, 1991 ; Sastry, 1995 ; Parain et al, 2001 ; Buccafusco and Terry, 2003 ; Koh et al, 2003 ; de Aguiar et al, 2013 ; Gao et al, 2014 ; Tiwari et al, 2015 ; Majdi et al, 2018 ).…”
Section: The Nicotinic Receptors and Neuronal Survival In The Pd Brainmentioning
confidence: 99%
“…Despite their structural similarities, nicotine, and cotinine, differ in their mechanism of action, properties, behavioral effects, and toxicity profile (nicotine is one hundred times more toxic than cotinine) ( Buccafusco and Terry, 2003 ; Grizzell and Echeverria, 2015 ; Majdi et al, 2018 ). The last decade of research has shown that cotinine has unique pharmacokinetic and pharmacodynamic properties, acting as a very weak nAChR agonist but a positive modulator of the α7nAChRs ( Moran, 2012 ; Grizzell et al, 2014 ; Sadigh-Eteghad et al, 2020 ).…”
Section: Effect Of Cotinine Preventing Amyloid-β Peptides Accumulation and Promoting Synaptic Plasticity In The Brainmentioning
confidence: 99%